AGRICULTURAL SECTOR MODELLING:ENHANCING THE DEVELOPMENT OF SMALLHOLDERS - Zainal Abidin Mohamed (UNEJ e-Proceeding, 2012)
This paper presents the benefit of using agricultural sector modeling (e.g. MAgPA) to enhance the development of smallholders in Malaysia. Malaysian Agricultural Policy Analysis (MAgPA) is an analytical tool to forecast major variables in the commodity sector as well as to simulate the impact of changes in macroeconomic variables both in the domestic and international fronts as well as other predetermined variables on the overallagricultural sector. The aims of MAgPA are: (i) to develop and build an empirical forecasting model for the agricultural sector as well as for the related agricultural commodities based on time series data and econometric models; (ii) to perform simulations for tracing responses of policy changes and to determine the impact of changes in the international environment on the Malaysian agricultural sector; (iii) to trainand build capacity of selected officers from related ministries and agencies the process of developing and building empirical forecasting model for the agricultural sector; and (iv) to prepare a complete manual for the purpose of developing and building a complete empirical forecasting model for Malaysian agriculture.